The Aluminum-Ion Battery: A Sustainable and Seminal Concept? - Leisegang, Tilmann; Meutzner, Falk; Zschornak, Matthias; Münchgesang, Wolfram; Schmid, Robert; Nestler, Tina; Eremin, Roman A.; Kabanov, Artem A.; Blatov, Vladislav A.; Meyer, Dirk C. (Frontiers in Chemistry, 2019)
The expansion of renewable energies and the growing number of electric vehicles and mobile devices demand for improved and low-price electrochemical energy storage. In order to meet the future needs for energy storages, novel material systems with highest energy densities, readily available raw materials, and safety are required. Currently, especially lithium and lead dominate the battery market, but apart from cobalt and phosphorous, lithium may show substantial supply challenges prospectively, as well. Therefore, the search for new chemistries will become increasingly important in the future in order to diversify battery technologies. But which materials seem promising? Using a selection algorithm for the evaluation of suitable materials, the concept of a rechargeable, high-valent all-solid-state aluminum-ion battery appears promising, in which metallic aluminum is used as the negative electrode. On the one hand, this offers the advantage of a (theoretically) four times higher volumetric capacity compared to the lithium analogue. On the other hand, aluminum is the most abundant metal in the earth's crust. There is a mature industry and recycling infrastructure, making aluminum very cost efficient. This would make the aluminum-ion battery an important contribution to the energy transition process, already started globally. So far, it has not been possible to exploit this technological potential, as suitable positive electrodes and electrolyte materials are still lacking. The discovery of inorganic materials with high aluminum-ion mobility––usable as solid electrolytes or intercalation electrodes––is a necessary innovation leap forward in the field of rechargeable high-valent ion batteries. In this review article, describe the constraints for a sustainable and seminal battery chemistry, we present an assessment of the chemical elements in terms of negative electrodes, comprehensively motivate utilizing aluminum, categorize the aluminum battery field, critically review the existing positive electrodes and solid electrolytes, present a promising path for an accelerated development of novel materials und address problems of scientific communication in this field.